Natural history of autoimmune thyroiditis. Issue 6260 (24th January 1981) - Tunbridge, W M; Brewis, M; French, J M; Appleton, D; Bird, T; Clark, F; Evered, D C; Evans, J G; Hall, R; Smith, P; Stephenson, J; Young, E
Abstract : One hundred and sixty-three asymptomatic people with thyroid antibodies or raised serum thyrotrophin (TSH) concentrations, or both, and 209 age-matched and sex-matched controls without either marker of thyroid disorder were followed up for four years to determine the natural history of autoimmune thyroiditis. Mildly raised TSH concentrations alone and the presence of thyroid antibodies alone did not significantly increase the risk of developing overt hypothyroidism during the four years compared with the controls. Overt hypothyroidism developed at the rate of 5% a year in women who initially had both raised TSH concentrations and thyroid antibodies. Prophylactic treatment with thyroxine may be justified in women found to have both markers of impending thyroid failure. The cost effectiveness of screening the adult population remains to be evaluated.